Variation Characteristics of Hydrothermal Resources Effectiveness Under the Background of Climate Change in Southern Rice Production Area of China - Qing YE; Xiao-guang YANG; Shu-wei DAI; Yong LI; Jian-ping GUO (Journal of Integrative Agriculture)
The spatiotemporal characteristics of hydrothermal resources in southern rice production area of China have changed under the background of climate change, and this change would affect the effectiveness of hydrothermal resources during local rice growing period. According to the cropping system subdivision in southern rice production area of China during 1980s, this study used climate data from 254 meteorological stations and phonological data from 168 agricultural observation stations in the south of China, and adopted 6 international evaluation indices about the effectiveness of hydrothermal resources to analyze the temporal and spatial characteristics of hydrothermal resources during the growing period of single cropping rice system and double cropping rice system for 16 planting zones in the whole study area. The results showed that: in southern rice production area of China, the effectiveness of thermal resources of single cropping rice area (SCRA) was less than that of double cropping rice area (DCRA), whereas the effectiveness of thermal resources of both SARA and DCRA showed a decreasing trend. The index value of effective precipitation satisfaction of SCRA was higher than that of DCRA, nevertheless the index value of effective precipitation satisfaction of both SCRA and DCRA showed a decreasing trend. There was a significant linear relationship between effective thermal resource and water demand, likely water demand increased by 18 mm with every 100°C d increase of effective heat. Effective precipitation satisfaction index (EPSI) showed a negative correlation with effective heat, yet showed a positive correlation with effective precipitation. EPSI reduced by 1% when effective heat resource increased by 125°C d. This study could provide insights for policy makers, land managers or farmers to improve water and heat resource uses and rationally arrange rice production activities under global climate change condition.